The Impact of Hegu Point (LI4) Acupressure Therapy and Warm Compress on Menstrual Pain (Dysmenorrhea) in Middle School Students - Agustini, IGA Ratih; Nilawati, Ni Kadek Ayu; Purwaningsih, Ni Komang (Future Science, 2024)
Introduction: Menstruation often leads to disturbances in women, with menstrual pain, or dysmenorrhea, being a common issue that affects daily activities. Non-pharmacological therapies like acupressure and warm compresses are considered safe and effective in managing dysmenorrhea. This study examines the effect of Hegu Point (LI4) acupressure therapy combined with warm compresses on menstrual pain in students at SMP Wisata Denpasar. Methods: This quantitative study employed a pre-experimental, one-group pre-test, and post-test design. The sample size was 52 students, selected through purposive sampling. The intervention involved applying a warm compress and acupressure at the Hegu point (LI4). Pain levels were measured using an observation sheet for pain scales, and the data were analyzed using the Wilcoxon rank test. Results: After the intervention, menstrual pain significantly decreased. Before the intervention, 57.7% of the students experienced moderate pain. After the intervention, 53.8% reported mild pain. The Wilcoxon test yielded a p-value of 0.000, indicating a significant effect. Conclusion: In students, Hegu Point (LI4) acupressure therapy combined with a warm compress significantly reduces menstrual pain. Healthcare providers should educate students about these non-pharmacological therapies for managing dysmenorrhea.